2012
DOI: 10.1016/j.envexpbot.2011.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Varying leaf-to-fruit ratios affect branch growth and dieback, with little to no effect on photosynthesis, carbohydrate or mineral pools, in different canopy positions of field-grown coffee trees

Abstract: a b s t r a c tHeavy bearing is a typical phenomenon on unshaded coffee (Coffea arabica L.) trees and limits both the production and retention of leaves, leading to branch dieback, and, thus, results in a strong biennial bearing pattern. The major goals of this study were to investigate the physiological mechanisms that may be associated with the leaf-to-fruit ratio (LFR), branch dieback, biennial production and the relationships between carbohydrate and mineral fluctuations and branch dieback in coffee plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 37 publications
(48 reference statements)
7
32
1
4
Order By: Relevance
“…This result was certainly associated with the grain formation stage of the coffee plants, when the requirement for nutrients is high. As fruits constitute preferential sinks for nutrients and photoassimilates (Laviola et al, 2008;Partelli, Espindola, Marré, & Vieira, 2014), vegetative growth is severely jeopardized during this stage, due to an accentuated imbalance in the source:sink ratio of these productive branches, despite these branches (PlagBB) possessing limited autonomy in the production and supply of carbohydrates, as verified for C. arabica (Chaves, Martins, Batista, Celin, & DaMatta, 2012). Additionally, the advent of new branches (budding) may reduce the growth of older branches (Ferreira et al, 2013) due to the changes in the source:sink relationship among different branches.…”
Section: Resultsmentioning
confidence: 96%
“…This result was certainly associated with the grain formation stage of the coffee plants, when the requirement for nutrients is high. As fruits constitute preferential sinks for nutrients and photoassimilates (Laviola et al, 2008;Partelli, Espindola, Marré, & Vieira, 2014), vegetative growth is severely jeopardized during this stage, due to an accentuated imbalance in the source:sink ratio of these productive branches, despite these branches (PlagBB) possessing limited autonomy in the production and supply of carbohydrates, as verified for C. arabica (Chaves, Martins, Batista, Celin, & DaMatta, 2012). Additionally, the advent of new branches (budding) may reduce the growth of older branches (Ferreira et al, 2013) due to the changes in the source:sink relationship among different branches.…”
Section: Resultsmentioning
confidence: 96%
“…This means that there was a higher dry matter partitioning for fruits over leaves and branches, and this was clearly confirmed by the linear increase in the fruit mass ratio (Figure 2 According to Cannell (1985), 20 cm 2 of leaf is required for each coffee fruit. However, Chaves et al (2012) showed that branch growth and total fruit production are reduced as RAFRr decreases, showing competition between vegetative and reproductive growth, the latter prevailing over the former, since fruits are priority sinks (CANNELL, 1985;LAVIOLA et al, 2007). In this study, the strong effect of spacing on RAFFr was demonstrated.…”
Section: Resultsmentioning
confidence: 54%
“…However, Chaves et al (2012) showed that branch growth and total fruit production are reduced as RAFRr decreases, showing competition between vegetative and reproductive growth, the latter prevailing over the former, since fruits are priority sinks (CANNELL, 1985;LAVIOLA et al, 2007). In this study, the strong effect of spacing on RAFFr was demonstrated.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations